2006
DOI: 10.1177/0021998306060174
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Slab Absorber: Absorption Efficiency and Theory Analysis

Abstract: Slab absorber is an important topic not only for military purposes but also for commercial application. Single-layer compact slab absorber cannot meet the required wave absorption in broad wave band besides some absorption peaks, and it is very necessary to develop a new kind of absorber to meet the need of absorption in broad wave band. In this study, a discrete slab absorber (DSA) has been developed by isolating conductive medium in absorbing matrix, and the reflection loss test indicates that the DSA exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The authors of [35] showed that the absorptive properties of slab absorbers could be improved by randomly distributing carbon black (CB) inclusions in them. Experimental results confirmed the significant improvement of the absorptive properties of such slabs (in a wide range of frequencies) in comparison with conventional absorbing slabs (not containing CB inclusions).…”
Section: Graphite Content By Volume (%)mentioning
confidence: 99%
“…The authors of [35] showed that the absorptive properties of slab absorbers could be improved by randomly distributing carbon black (CB) inclusions in them. Experimental results confirmed the significant improvement of the absorptive properties of such slabs (in a wide range of frequencies) in comparison with conventional absorbing slabs (not containing CB inclusions).…”
Section: Graphite Content By Volume (%)mentioning
confidence: 99%
“…According to literature (Duan et al 2006), the attenuation of the incident wave can be expressed approximately as…”
Section: Theory Analysismentioning
confidence: 99%
“…While attempts at discretizing continuous MAMs have been made, efficiently expanding bandwidth, achieving optimal outcomes has remained challenging. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The advent of metamaterial absorbers (MMAs), initiated by Landy's perfect MMA in 2008, 30 introduced a new avenue. Early metal-based MMAs relied on single-order resonance of subwavelength structures, displaying narrowband performances.…”
Section: Introductionmentioning
confidence: 99%